Simulating the prospects of technological catching up - Caldas, José Castro (2009)
Local increasing returns associated with static and dynamic scale effects, knowledge spillovers, polarization effects and the distance that separates different regions are among the most important driving forces behind the dynamics of economic and technological convergence. This paper puts forward a computational simulation model that seeks to integrate these factors. The modelling exercise was designed in order to achieve a better understanding of the relationship between the aspects underlying the specific trajectories of regional technological accumulation and the aggregate convergence/divergence patterns stemming from these trajectories. In particular, the role of history and geography in the dynamics of technological convergence is emphasized.